2010
DOI: 10.1111/j.1365-2249.2010.04217.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased programmed death-ligand-1 expression in human gastric epithelial cells inHelicobacter pyloriinfection

Abstract: Summary B7-H1 [programmed death-ligand-1 (PD-L1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 32 publications
5
72
0
1
Order By: Relevance
“…2A). Studies showed that PD-L1 was detectable in human gastric epithelial cells (17) and colonic epithelial cells (13,15,18). We confirmed that PD-L1 mRNA and protein were constitutively expressed in freshly isolated small intestinal epithelial cells (IECs) from naïve WT mice ( Supplementary Fig.1).…”
Section: Sepsis Increases Pd-l1 Expression In the Mouse Intestinesupporting
confidence: 63%
See 2 more Smart Citations
“…2A). Studies showed that PD-L1 was detectable in human gastric epithelial cells (17) and colonic epithelial cells (13,15,18). We confirmed that PD-L1 mRNA and protein were constitutively expressed in freshly isolated small intestinal epithelial cells (IECs) from naïve WT mice ( Supplementary Fig.1).…”
Section: Sepsis Increases Pd-l1 Expression In the Mouse Intestinesupporting
confidence: 63%
“…Figure 4C Accumulating evidence has demonstrated that the PD-1/PD-L1 pathway plays an important role in regulating the immune-inflammatory response during sepsis, as sepsis can up-regulate PD-L1 expression on a variety of immune cells both in humans (2,14). In the gastrointestinal tract, human gastric epithelial cells express basal levels of PD-L1, and its expression is significantly increased when exposed to Helicobacter Pylori (17). Importantly, the current study is the first report to show that the expression of PD-L1 is markedly elevated in the colon of patients with sepsis.…”
Section: Junction Integritymentioning
confidence: 99%
See 1 more Smart Citation
“…Programmed death 1 (PD-1), a negative regulator for activation, expansion and acquisition of effector functions of T cells, is well involved in pathogen evasion strategies [33,34]. Although extensive studies have been performed on function of PD-1, as so far regulation mechanism of PD-1 expression has not been reported.…”
Section: Pathogen Evasionmentioning
confidence: 99%
“…Flow cytometry analysis was performed using a technique described previously (14). The CD4 ϩ T cells were gated from the forward scatter (FSC) low versus CD4 ϩ T cells, which correspond to the lymphocyte population according to our previous data (15).…”
mentioning
confidence: 99%